Room of silence: an explorative investigation of design students' redesign of an arena for reflection and existential meaning-making. (2nd April 2016) - Petersson, Anna; Sandin, Gunnar; Liljas, Maria
Abstract: This paper explores design students' proposals for a redesign of the interior of a room of silence at the SUS hospital in Malmö. Reflection and existential meaning-making are discussed in relation to the material culture of design, and more specifically in relation to four different themes found among the students' proposals: nature as common symbolic framework and salutary force; lighting creating a visual and spatial ambience for retreat; interactive objects allowing ritualised activities; and the presence and absence of religious symbols. In this paper, we argue that architecture and design more profoundly could support people with varying existential viewpoints when it comes to providing religiously and culturally shared public spaces for dealing with existentially crucial moments. We also argue for an interdisciplinary research approach to healing environments, where existential meaning-making is included in the overall discussion of the design of health care architecture.